Transporte eletrônico de nanofita de grafeno sob a influência de constrições e oxidação - SOUSA, Mario Edson Santos de (Universidade Federal do Pará, 2015)
In this work we investigate the effects of oxidative functionalization groups on the structure of graphene nanoribbons and also the effects of constrictions caused by the emergence of a nanopore to the tape, where these effects were analyzed by means of electron transport via longitudinal external field center. Our calculations were parameterized by the semi-empirical model of the theory of extended Huckel-ETH, adopting the method of Green's functions of non equilíbrio- NEGF. The currents were calculated through the Landauer equation that uses the transmission function of the region spreader to the flow of electrons with energy E coming out of the electrode. By means of this approach, it was possible to analyze the behavior of charge carriers in each of the proposed devices, as well as the nature of such behavior. Were found to curves I(V) two transport regimes: Ohmic and NDR, checking maximum current and also the threshold voltage (VTh1 <VTh2 <VTh3 <VTh4) in which occurs the regime change of transport for the nanoribbon (without oxidizing, high oxidation and low average oxidation, respectively) located suggests that due to the presence of two nanoconstrições in the graphene nanoribbon as regions of quantum confinement and electronic proportional states at the functionalization. It was observed that the center pore of the tape has created two nanoconstrições in the sides of the ribbon, thus allowing the electronic confinement devices based on these ribbons, characterizing it as a resonant tunneling diode DRT verified by the peak / valley ratio. We can conclude that our proposed device is according to experimental results for nanodevices and their applicability not be restricted on the oxidation states, being a positive factor that contributes to the phenomenological aspects of electronic transport in graphene and fabrication of nanodevices low cost.